Characteristics of microbial community and aroma compounds in traditional fermentation of Pixian broad bean paste as compared to industrial fermentation. (10th January 2018) - Li, Xiyang; Zhao, Changsong; Zheng, Chao; Liu, Jian; Vu, Viet Ha; Wang, Xianding; Sun, Qun
ABSTRACT: Traditionally fermented Pixian broad bean paste (PBP) is a traditional condiment in China and is recognized to have superior quality than the industrially fermented. This work aimed to identify the dominant microbes and unique aroma compounds in traditionally fermented PBP with respect to those in the industrially fermented one. Results showed that several species of lactic acid bacteria, yeasts, Aspergillus, molds, and Staphylococcus were only detected in traditionally fermented PBP, namely, Leuconostoc lactis, Staphylococcus xylosus, S. succinus, Amylomyces rouxii, Mucor genevensis, Absidia corymbifera, Issatchenkia orientalis, basidiomycete yeast sp., and Metschnikowia pulcherrima . Furthermore, the traditionally fermented PBP contained more compounds that contribute to its aroma than those in industrially fermented PBP. A total of 28 aroma substances only were detected in the traditionally fermented PBP. Among these substances, seven were considered aroma-active compounds, namely, ethyl caprylate, hexadecanoic acid methyl ester, 2-methyl-pyrazine, 2, 6-dimethyl- pyrazine, 2-pentyl furan, 2-acetyl furan, and hexadecanoic acid. This work provides useful information on the microbial composition and aroma compounds of PBP that can be used to upgrade the quality of industrially fermented PBP.